2015
DOI: 10.1111/cob.12107
|View full text |Cite
|
Sign up to set email alerts
|

Educational level and chronic inflammation in the elderly – the role of obesity: results from the population‐based CARLA study

Abstract: This study aimed to assess the mediating role of anthropometric parameters in the relation of education and inflammation in the elderly. Cross-sectional data from the population-based CARdio-vascular Disease, Living and Ageing in Halle study were used after excluding subjects with a plasma level of high-sensitive C-reactive protein (hsCRP) above 10 mg L(-1) (916 men/760 women remaining). Education was categorized in accordance with International Standard Classification of Education. As inflammation parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This was confirmed in our analysis, with BMI, HbA 1c and smoking being associated with hsCRP. We also found that the use of lipid-lowering therapy and higher levels of education were negatively associated with hsCRP, which have been shown previously [40][41][42].…”
Section: Discussionsupporting
confidence: 86%
“…This was confirmed in our analysis, with BMI, HbA 1c and smoking being associated with hsCRP. We also found that the use of lipid-lowering therapy and higher levels of education were negatively associated with hsCRP, which have been shown previously [40][41][42].…”
Section: Discussionsupporting
confidence: 86%
“…Substantial reductions in CRP were predicted with a 1 mmol/L change in HDL-c; however, eliciting this response may prove difficult in a resource-poor environment. These covariates, however, do predict possible routes of intervention, whereby proper nutrition (focusing on weight management, treatment of hyperlipidemia, and glycemic control), as well as increased physical activity (to improve resting heart rate) and increasing education levels, can reduce inflammation in populations [ 35 , 36 , 37 ]. Completing 12 or more years of formal education was associated with reduced CRP concentrations ( Table 1 , unadjusted), although this reduction was found to be non-significant.…”
Section: Discussionmentioning
confidence: 99%